Students’ Perception of the Effects, Satisfaction, and Challenges of Technology-Enabled Active Learning (TEAL) - Ab Razak, Nur Ain Shuhada; Lai, Chee Sern; Talibin, Md Najip (Online Journal for TVET Practitioners, 2026)
This study was conducted to explore students’ perceptions of the use of Technology-Enabled Active Learning (TEAL) in terms of its effects, satisfaction, and challenges in teaching and learning at the Faculty of Technical and Vocational Education (FPTV), Universiti Tun Hussein Onn Malaysia. The objectives of this study were to identify students’ perceptions regarding the effects of TEAL implementation, their satisfaction throughout the learning process using this approach, and the challenges encountered. Additionally, the study aimed to examine whether there were differences in perceptions based on gender across these three aspects. This study employed a quantitative survey design, and data were collected through a questionnaire, which was validated by experts and tested for reliability, yielding a Cronbach’s Alpha value above 0.8. The sample consisted of 287 undergraduate students from 14 academic programs at FPTV, selected using simple random sampling. Data were analyzed using descriptive statistics (mean and standard deviation) to address the three research questions and the Mann-Whitney U test to examine gender-based differences. The findings revealed that students’ perceptions of the effects of TEAL were high (mean = 4.45), as were their satisfaction levels (mean = 4.39), while perceived challenges were moderate (mean = 3.56). Inferential analysis showed that there were no significant differences between male and female students in terms of their perceptions of the effects, satisfaction, and challenges associated with TEAL. The implications of this study suggest that TEAL has the potential to enhance student engagement, understanding, and overall learning satisfaction if implemented systematically and holistically. Therefore, it is recommended that the faculty strengthen training related to technology use for both lecturers and students, improve technological infrastructure, and restructure instructional strategies to create a more interactive and conducive learning environment. These efforts would enable the full optimisation of technology-enabled active learning in the context of higher education.